2016
DOI: 10.18052/www.scipress.com/ilns.56.82
|View full text |Cite
|
Sign up to set email alerts
|

Antibacterial Potentials of Ve<i>rnonia amygdalina</i> against Antibiotic-Resistant <i>Salmonella</i> Specie Isolated from Nworie River, Imo State, Nigeria

Abstract: ABSTRACT. Salmonella species were isolated from Nworie River and then tested against several antibiotics to include; Gentamycin, Streptomycin, Amoxycillin, Kanamycin, Oxacillin, Ofloxacin, Imipenem, Ciprofloxacin, Aztreonam and Ceftazidime. Salmonella isolates obtained from the river were resistant to at least three different antibiotics. All isolates were resistant to Amoxycillin, Oxacillin and Iminipem showing a 100% resistant rate, while showing sensitivity to Ciprofloxacin, Aztreonam, Gentamycin, Ceftazidi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 14 publications
0
2
0
Order By: Relevance
“…Whereas the insensitivity of Salmonella bacilli to aqueous extracts of C. papaya leaves has been reported [21,22]. Chikwendu et al [23] also concluded that aqueous extract of roots, stem and leaves of V. amygdalina has no anti-salmonolla effects.…”
Section: Discussionmentioning
confidence: 99%
“…Whereas the insensitivity of Salmonella bacilli to aqueous extracts of C. papaya leaves has been reported [21,22]. Chikwendu et al [23] also concluded that aqueous extract of roots, stem and leaves of V. amygdalina has no anti-salmonolla effects.…”
Section: Discussionmentioning
confidence: 99%
“…Aqueous extracts of the leaf, stem and roots showed no activity against antibiotic resistant Salmonella isolate, while the ethanol and acetone extracts showed activity rates of 20% and 17% for roots, 14.3% and 12.9% for stem, and, 15.7% and 11.4% for leaf [44]. The anti-Salmonella activity has been further confirmed by the ethanolic extract [50,51].…”
Section: Vernonia Amygdalinamentioning
confidence: 99%